Krisis Etika Demokrasi Politik Elektoral: Upaya Restorasi Keadaban Dalam Sistem Ketatanegaraan - Prabaningtyas, Farisha Dian; Wulandari, Sri (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2025)
This article aims to examine the ethical crisis in electoral politics in Indonesia and its implications for the nation's constitutional system. Electoral democracy, as the embodiment of people's sovereignty, has recently been challenged by political behavior that prioritizes identity politics, hoaxes, and transactional practices. The urgency of writing this article is based on the moral decline in political competition during elections, especially ahead of the 2024 presidential election. Using normative juridical methods with a conceptual and statutory approach, this article analyzes the role of political institutions and the legal framework in restoring ethical democracy. The results show that Indonesiaâ€™s electoral process still lacks an ethical foundation that can produce statesmanlike leaders. Thus, revitalizing the function of political parties, strengthening the role of electoral institutions, and embedding moral education in political recruitment are critical steps toward a dignified democratic system. electoral politicsÂ